Pediatric Hospitalizations After School Reopening During the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Alpha (B.1.1.7) Variant Spread: A Multicenter Cross-sectional Study in Israel. (29th January 2022) - Friedman, Nir; Levy, Nitai; Kaplan, Or; Padeh, Gabi; Krupik, Danna; Jacob, Ron; Gamsu, Shirly; Weiser, Giora; Cohen, Naama Kuchinski; Schnapp, Zeev; Cohen, Noy; Feldman, Oren; et al.
Abstract: This multicenter, cross-sectional study provides evidence on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–associated emergency department visits and hospitalizations in pediatric wards and intensive care units after school reopening during the SARS-CoV-2 Alpha (B.1.1.7) variant spread in Israel. Study findings suggest that school reopening was not followed by an increase in SARS-CoV-2–related pediatric morbidity.